Electrode and power storage device

A membrane of silicon-bonded organic and inorganic compounds on the active material surface addresses thermal stability and resistance issues, enhancing the electrode's performance by preventing electrolyte decomposition and passive film formation.

JP2024175744APending Publication Date: 2024-12-19NITERRA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023093709
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-07
Publication Date
2024-12-19

AI Technical Summary

Technical Problem

Existing electrodes and power storage devices face challenges in achieving improved thermal stability while maintaining low internal resistance.

Method used

A membrane comprising a silicon-bonded organic compound and a silicon-bonded inorganic compound is applied to the surface of the active material, with a molar ratio of 25:75 to 75:25 and an atomic concentration of silicon at 0.1 atm% or more, enhancing the thermal stability and reducing internal resistance.

Benefits of technology

The film improves thermal stability and maintains low internal resistance, preventing electrolyte decomposition and passive film formation, thereby extending the life of the active material layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024175744000001_ABST
    Figure 2024175744000001_ABST
Patent Text Reader

Abstract

To provide an electrode capable of improving heat stability while maintaining low inner resistance, and provide a power storage device.SOLUTION: An electrode comprises: a collector; and an active material layer adhered to the collector. In the electrode, the active material layer contains an active material, and at least one part of a front surface of the active material is covered with a film. The film contains: an organic chemical compound to which a silicon is coupled; and an inorganic chemical compound to which the silicon is coupled. A power storage device contains the electrode.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode and an electricity storage device that include an active material. [Background technology]

[0002] In an electrode including a current collector and an active material layer attached to the current collector, the prior art disclosed in Patent Document 1 has an active material contained in the active material layer covered with a film containing silicone. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2016-81922 A Summary of the Invention [Problem to be solved by the invention]

[0004] There is a need in the prior art for further improvements in the thermal stability of active materials.

[0005] The present invention has been made in response to this demand, and has an object to provide an electrode and an electricity storage device that can improve thermal stability while maintaining low internal resistance. [Means for solving the problem]

[0006] A first aspect to achieve this objective is an electrode comprising a current collector and an active material layer attached to the current collector, the active material layer including an active material, at least a portion of a surface of the active material being covered with a membrane, the membrane including a silicon-bonded organic compound and a silicon-bonded inorganic compound.

[0007] In a second embodiment, in the first embodiment, the molar ratio of the organic compound to the inorganic compound is from 25:75 to 75:25.

[0008] A third aspect is the first or second aspect, wherein the atomic concentration of silicon contained in the film is 0.1 atm % or more.

[0009] In a fourth aspect, in any one of the first to third aspects, the active material is one or more selected from porous carbon, natural graphite, artificial graphite, graphitizable carbon, non-graphitizable carbon, and carbon fiber.

[0010] A fifth aspect is an electricity storage device including the electrode according to any one of the first to fourth aspects. Effect of the Invention

[0011] According to the electrode and electricity storage device of the present invention, the film covering at least a portion of the surface of the active material contains a silicon-bonded organic compound and a silicon-bonded inorganic compound, so that in an electrode containing an active material covered with a film of an organosilicon compound, it is possible to improve thermal stability while maintaining a low internal resistance. [Brief description of the drawings]

[0012] [Figure 1] 1 is a cross-sectional view of an electricity storage device according to an embodiment. [Diagram 2] FIG. 2 is a cross-sectional view of an active material layer. [Diagram 3] FIG. 1 is a schematic diagram of a membrane. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, preferred embodiments of the present invention will be described with reference to the accompanying drawings. FIG. 1 is a schematic cross-sectional view of an electricity storage device 10 in one embodiment. The electricity storage device 10 includes an electrode (negative electrode) 11, a positive electrode 15, and a separator 14 that separates the negative electrode 11 from the positive electrode 15. FIG. 1 illustrates an electricity storage device 10 having one set of the negative electrode 11, the separator 14, and the positive electrode 15, but the present invention is not limited to this, and the electricity storage device 10 may include a plurality of sets of these. In addition, the electricity storage device 10 is not limited to one having a stacked structure, and may be one having a wound structure in which the negative electrode 11 and the positive electrode 15 are stacked and wound with the separator 14 interposed therebetween.

[0014] The electricity storage device 10 is a device in which carrier ions present in an electrolyte move to release electric charge. Examples of the electricity storage device 10 include a lithium ion capacitor, a lithium ion battery, a lithium-sulfur battery, a sodium ion battery, and a metal-air battery. Hereinafter, an example of the electricity storage device 10 is a lithium ion capacitor in which lithium ions are carrier ions.

[0015] Negative electrode 11 includes a sheet-shaped current collector 12 and an active material layer 13 attached to current collector 12. There are no particular limitations on the material of current collector 12, but examples include Cu, Al, a Cu alloy, an Al alloy, and stainless steel.

[0016] The positive electrode 15 is formed by stacking a current collector 16 and an active material layer 17. Examples of the material for the current collector 16 include a metal selected from Ni, Ti, Fe, and Al, an alloy containing two or more of these elements, and stainless steel.

[0017] The active material layer 17 contains an active material such as graphite or activated carbon, and a conductive agent. Examples of the conductive agent include carbon black, acetylene black, ketjen black, and carbon fiber. The active material may be any material that can reversibly support anions, and is not limited to graphite or activated carbon.

[0018] The active material layer 17 may contain a binder that binds the active material and the conductive agent. Examples of the binder include fluororesin, polyolefin, polyvinylpyrrolidone, polyvinyl alcohol, cellulose ether, and rubber such as styrene butadiene rubber. Examples of the fluororesin include vinylidene fluoride polymers, polychlorotrifluoroethylene, polyvinyl fluoride, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymers, tetrafluoroethylene-hexafluoropropylene copolymers, ethylene-tetrafluoroethylene copolymers, and ethylene-chlorotrifluoroethylene copolymers.

[0019] The separator 14 is made of a porous material that is durable against the active material and electrolyte contained in the positive electrode 15 and the negative electrode 11, and that has no electronic conductivity while allowing carrier ions to pass through. Examples of the separator 14 include nonwoven fabrics and porous membranes made of cellulose, polypropylene, polyethylene, etc.

[0020] The electrolyte solution has carrier ions present in a solvent. The solvent of the electrolyte solution is not particularly limited as long as it is liquid in the temperature range in which the electricity storage device 10 is used. Examples of the solvent include carbonate esters, aliphatic carboxylate esters, phosphate esters, γ-lactones, ethers, nitriles, sulfolane, dimethyl sulfoxide, fluorous solvents, and ionic liquids. A mixture of these may also be used.

[0021] FIG. 2 is a cross-sectional view of the active material layer 13 of the negative electrode 11. The active material layer 13 includes an active material 18. There is no limitation on the material of the active material 18 as long as it can absorb and release carrier ions. Examples of the material of the active material 18 include carbon-based materials such as porous carbon, natural graphite, artificial graphite, graphitizable carbon (hard carbon), non-graphitizable carbon (soft carbon), and carbon fiber, Si, Si-Li alloys, and compounds containing Si and O as constituent elements (hereinafter referred to as "SiOx", where 0.5≦X≦1.5). Examples of SiOx (silicon oxide) include oxides of Si and those having a structure in which microcrystalline or amorphous Si is dispersed in an amorphous SiO2 matrix. One or more of these materials are selected as the active material 18, but it is preferable that at least one of them is a carbon-based material in which carrier ions are inserted between layers during charging.

[0022] Since SiOx has poor electrical conductivity, it is preferable to provide a conductive layer covering the surface of SiOx or to combine SiOx with a conductive material. The means for combining SiOx with a conductive material is granulation. The material of the conductive layer is exemplified by metals such as Pt and Os, and carbon. The conductive material is exemplified by graphite, low crystalline carbon, graphitizable carbon, non-graphitizable carbon, carbon black, carbon nanotubes, carbon fiber, and fibrous or coiled metal.

[0023] When the conductivity of the active material 18 is low, a conductive agent is mixed and dispersed in the active material layer 13 to create a conductive network in order to reduce isolated active material 18. Examples of the conductive agent include carbon black, acetylene black, ketjen black, carbon nanotubes, and fibrous or coiled metals.

[0024] At least a portion of the surface of the active material 18 is covered with an insulating film 19. The film 19 reduces decomposition of the electrolyte on the surface of the active material 18, and reduces the formation of a passivation film on the surface of the active material 18 due to reductive decomposition of the electrolyte.

[0025] It is preferable that membrane 19 is permeable to carrier ions so as not to impede the diffusion of carrier ions through membrane 19. This is to reduce the internal resistance of active material layer 13. The thickness of membrane 19 is preferably 0.1 nm or more and 1 μm or less, more preferably 0.1 nm or more and 50 nm or less, and even more preferably 0.1 nm or more and 5 nm or less, so as not to impede the diffusion of carrier ions.

[0026] Fig. 3 is a schematic diagram of the film 19. In Fig. 3, black circles represent Si (silicon atoms) and white circles represent O (oxygen atoms). In Fig. 3, in order to simplify the three-dimensional structure of the compounds constituting the film 19 and show it on a plane, some of the bars indicating the shared electron pairs between atoms are omitted. The film 19 contains an inorganic compound 21 to which Si is bonded and an organic compound 22 to which Si is bonded.

[0027] In this embodiment, the film 19 further includes a carbon compound 23 bonded to C. The carbon compound 23 is a compound having a chain structure or a ring structure of C. The carbon compound 23 may have a straight chain structure, a branched structure, a ring structure, or a composite structure of these. The carbon compound 23 is bonded to Si of the inorganic compound 21 or the organic compound 22. The carbon compound 23 modifies the inorganic compound 21 or the organic compound 22.

[0028] Examples of the inorganic compound 21 (inorganic silicon compound) include glass containing Si, amorphous silica such as silica gel, crystalline silica, and zeolite in which a part of the Si in crystalline silica is replaced with Al. Silica has a structure in which SiO4 tetrahedrons are connected three-dimensionally by sharing oxygen atoms. In addition to Si, the glass may contain alkali metals such as Na, Li, Ca, alkaline earth metals, and transition metals such as Ti.

[0029] The organic compound 22 is an organosilicon compound having a Si-C bond in the molecule. Examples of the organic compound 22 include a siloxane compound having a siloxane bond (Si-O-Si) and a silicone having a siloxane bond as the main skeleton and an organic group such as an alkyl group or an aryl group bonded to Si.

[0030] The inorganic compound 21 is bonded to the organic compound 22 by a covalent bond such as a Si-C bond. When the bond between the inorganic compound 21 and the organic compound 22 is a Si-C bond, the film 19 is less likely to be decomposed because the Si-C bond has a larger bond energy than a C-C bond. The structure of the film 19 is as follows: 29 It can be analyzed using Si-NMR (nuclear magnetic resonance spectroscopy) and X-ray diffraction methods.

[0031] Since the inorganic compound 21 and the organic compound 22 have excellent insulating properties, by providing the film 19 containing the inorganic compound 21 and the organic compound 22 on the surface of the active material 18, it is possible to reduce electrochemical decomposition of the electrolyte in the active material layer 13. Since the formation of a passivation film on the active material layer 13 can be reduced, it is possible to reduce a decrease in the discharge capacity of the electricity storage device 10 due to the formation of the passivation film.

[0032] When the volume of active material 18 changes during charging and discharging, it is preferable that film 19 follows the change in shape caused by the volume change of active material 18 in order to reduce peeling of film 19. Since film 19 contains organic compound 22, organic compound 22 deforms, allowing film 19 to follow the change in shape caused by the volume change of active material 18.

[0033] When the organic compound 22 contains silicone, the adhesion between the active material 18 and the organic compound 22 can be improved by selecting the hydrophilic or hydrophobic nature of the organic group of the silicone depending on the material of the active material 18. Examples of the hydrophobic organic group include a phenyl group and an alkyl group. Examples of the hydrophilic organic group include a hydroxyl group, a carboxyl group, a sulfo group, and an amino group.

[0034] Film 19 has excellent heat resistance because it contains inorganic compound 21. The higher the environmental temperature, the more the active material layer 13 deteriorates, but since the heat resistance (thermal stability) of film 19 can be improved, the life of active material layer 13 can be extended.

[0035] The molar ratio of inorganic compound 21 to organic compound 22 contained in film 19 is preferably 25:75 to 75:25. This is because the inorganic compound 21 and organic compound 22, which have different chemical properties, complement each other in terms of their advantages. The atomic concentration of silicon contained in film 19 is preferably 0.1 atm % or more. This is because this stabilizes the bonds in film 19. The molar ratio of inorganic compound 21 to organic compound 22 and the atomic concentration of silicon can be analyzed by X-ray photoelectron spectroscopy (XPS).

[0036] Returning to FIG. 2, the active material layer 13 contains a binder 20 and a thickener as optional components. Examples of the binder 20 include fluororesin, acrylic resin, polyolefin, and rubber. Examples of the fluororesin include polytetrafluoroethylene, polyvinylidene fluoride, and vinylidene fluoride-hexafluoropropylene copolymer. Examples of the polyolefin include polyethylene and polypropylene. Examples of the rubber include styrene-butadiene rubber. Examples of the thickener include carboxymethyl cellulose.

[0037] Since the film 19 containing the inorganic compound 21 has high adhesiveness to the binder 20, the adhesion between the film 19 and the binder 20 is maintained even if the active material 18 and the binder 20 expand. Since the adhesion of the active material 18 is maintained by the binder 20, the structure of the active material layer 13 is maintained.

[0038] The synthesis of the film 19 on the surface of the active material 18, i.e., the composite of the inorganic compound 21 and the organic compound 22 on the active material 18, can be carried out, for example, by hydrolyzing a mixture of some alkoxides and the active material 18. The alkoxides that can be used include trifunctional alkoxysilanes [R'Si(OR)3] and tetrafunctional silicon alkoxides [Si(OR)4]. R represents an alkyl group.

[0039] In addition, a silanol group (-SiOH) or a trialkoxysilyl group (-Si(OR)3) can be introduced into an organic polymer, and a film 19 in which an inorganic compound 21 and an organic compound 22 are covalently bonded to each other by a condensation polymerization reaction with silicon alkoxide in a sol-gel process can be provided on the surface of an active material 18, or a silane coupling agent containing silicon and having an organic reactive portion and an inorganic reactive portion can be reacted with the active material 18 to obtain the film 19.

[0040] The negative electrode 11 is manufactured, for example, as follows. A slurry containing the active material 18 as an essential component, and a binder and a thickener as optional components, which are dispersed in a dispersion medium is prepared. The dispersion medium is exemplified by an organic solvent such as N-methyl-2-pyrrolidone or water. The prepared slurry is applied to the current collector 12, and the slurry is dried to obtain the active material layer 13. The dried active material layer 13 may be rolled with a roller or the like. Next, a coupling treatment is performed on the active material layer 13 by an atmospheric pressure gas phase method or a vacuum gas phase method using a silane coupling agent, and a film 19 is provided on the surface of the active material 18. Li may be supplied to the surface of the active material layer 13 to pre-dope the Li in an amount equivalent to at least a part of the irreversible capacity.

[0041] The electricity storage device 10 is manufactured, for example, as follows. A slurry is prepared by dispersing an active material and a conductive agent in a solution in which a binder is dissolved. After tape casting on a current collector 16, the resulting product is dried to obtain a green sheet (positive electrode sheet) for the positive electrode 15. The separator 14, the positive electrode sheet, and the negative electrode 11 are each cut into a predetermined shape, and then the positive electrode sheet, the separator 14, and the negative electrode 11 are stacked in this order, and terminals (not shown) are connected to the current collectors 12 and 16, respectively, and the resulting product is enclosed in a case (not shown) together with an electrolyte, to obtain an electricity storage device 10 including the positive electrode 15, the separator 14, and the negative electrode 11, in that order. EXAMPLES

[0042] The present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0043] (Preparation of negative electrode) 94 parts by mass of graphite, 5 parts by mass of styrene butadiene rubber (binder), and 1 part by mass of carboxymethyl cellulose (thickener) were added to 100 parts by mass of pure water and mixed with a mixer to prepare a slurry. A total mass of the graphite, binder, and thickener was 6.5 mg / cm on a current collector made of 8 μm thick copper foil. 2 The slurry was applied so as to obtain a negative electrode, and the active material layer was formed by vacuum drying at 70° C. for 1 hour.

[0044] A solution (silane coupling agent) of a mixture of dimethoxydimethylsilane, a reagent for a silicon-bonded organic compound, and tetramethoxysilane, a reagent for a silicon-bonded inorganic compound, and a negative electrode were placed in a container, and the negative electrode was arranged so that the active material layer appeared in the space inside the container. After sealing the container, the solution was heated to 80°C under atmospheric pressure to vaporize the solution. After the active material layer was placed in an atmosphere of a mixed gas of the vapor of the solution and the air for a certain period of time, the negative electrode was taken out of the container and heated at 150°C in the air for 1 hour to obtain a negative electrode in Sample No. 1-12 shown in Table 1, in which a film containing at least one of an organic compound and an inorganic compound was formed on the surface of the material contained in the active material layer. Sample No. 13 is a negative electrode that was not treated with a silane coupling agent (a negative electrode in which the active material is not covered with a film) and was prepared for comparison.

[0045] [Table 1]

[0046] In Sample No. 1-12, the molar ratio of the organic and inorganic compounds contained in the film was set by adjusting the mixing ratio of the two reagents. The atomic concentration of Si contained in the film was adjusted by the length of time that the active material layer was placed in the atmosphere of a mixture of the vapor of the solution and air. The time that the negative electrode was placed in the atmosphere is shown in Table 1.

[0047] (Preparation of positive electrode) 80.7 parts by mass of activated carbon, 18.3 parts by mass of acetylene black (conductive agent), and 5.5 parts by mass of polyacrylic acid (binder) were added to 317 parts by mass of pure water and mixed in a mixer to prepare a slurry. The total mass of the activated carbon, conductive agent, and binder was 5.0 mg / cm on a current collector made of 18 μm thick aluminum foil. 2 The slurry was applied so as to obtain a positive electrode, and the active material layer was formed by vacuum drying at 70° C. for 1 hour.

[0048] (Cell Preparation) The negative electrode was cut into a square with a side length of 25 mm, and a square Li metal foil with a side length of 25 mm was placed on top of the active material layer, and then sandwiched between the separators. The electrolyte was injected into the separator, and the half cell was then sealed in a vacuum to create a half cell. The electrolyte was lithium bis(fluorosulfonyl)imide (LiFSI) dissolved in a lithium salt (1 mol / dm 3 The half-cell was charged at a constant current of 0.1 C rate to 0 V, and then charged at a constant voltage of 0.01 C to perform pre-doping.

[0049] The negative electrode, separator, and positive electrode cut into a square with a side length of 20 mm were stacked in this order from the disassembled half cell, placed in a soft packaging bag with aluminum vapor deposition, and electrolyte was injected to prepare a semi-finished cell. The electrolyte was lithium bis(fluorosulfonyl)imide (LiFSI) in a lithium salt (1 mol / dm 3 The semi-finished products were aged by applying a potential of 3.8 V for 48 hours, after which the gas generated in the soft packaging bag during aging was sucked out and the bag was sealed in a vacuum to obtain two cells each containing the negative electrode of Sample No. 1-13.

[0050] (Determination of initial resistance) For the cells of Sample No. 1-13, after charging and discharging at a constant current of 50C, the resistance (initial resistance) was obtained from the voltage change and current immediately after the discharge was stopped by the DC method. In order to investigate the effect of the film on the surface of the active material on the formation of the passive film, the initial resistance of Sample No. 13 was used as the standard, and the initial resistance of each sample was subtracted from the initial resistance of Sample No. 13, and the value was divided by the initial resistance of Sample No. 13 to calculate the percentage (%). A ratio of less than 3% was determined as A, a ratio of 3% to less than 5% was determined as B, a ratio of 5% to less than 10% was determined as C, and a ratio of 10% or more was determined as D. The results are shown in the column for initial resistance in Table 1.

[0051] (Measurement of Si atomic concentration) The cell of sample No. 1-12 in which the initial resistance was measured was disassembled, the negative electrode was removed, and the negative electrode was immersed in dimethyl carbonate for 5 minutes to remove the electrolyte adhering to the active material layer. The active material layer was sealed in a transfer vessel under an Ar atmosphere, and then the surface of the active material layer was analyzed by XPS to calculate the atomic concentration (atm%) of silicon contained in the film. The XPS conditions were: X-ray: monochromated AlKα radiation, pass energy: 140 eV, analysis area: 100 μmΦ. The results are shown in the column for Si atomic concentration in Table 1.

[0052] (Measurement of the molar ratio of organic to inorganic compounds) After peak fitting was performed on the Si2p narrow spectrum obtained by XPS measurement of the surface of the active material layer, the molar ratio of organic and inorganic compounds was calculated from the ratio of the area intensity of the 101 eV peak intensity originating from the inorganic compound of Si to the area intensity of the 104 eV peak intensity originating from the organic compound of Si. The XPS conditions were: X-ray: monochromated AlKα radiation, pass energy: 140 eV, analysis area: 100 μmΦ. The results are shown in the organic and inorganic compounds columns in Table 1.

[0053] (Determination of high temperature characteristics) A test was conducted on the cell of sample No. 1-13 by applying a potential of 3.8V for 500 hours in a thermostatic chamber maintained at 85°C. During the test, the temperature of the thermostatic chamber was lowered to room temperature every 125 hours, the cell was removed from the thermostatic chamber, and the volume of the cell swelled by the gas was measured by the Archimedes method to check the amount of gas generated by the reaction between the active material and the electrolyte. The test time at which the ratio of the value obtained by subtracting the volume of the cell before the test from the volume of the cell during the test, divided by the volume of the cell before the test, reached 50% or more was examined. Test times exceeding 500 hours were judged as A, test times exceeding 375 hours but not exceeding 500 hours were judged as B, test times exceeding 250 hours but not exceeding 375 hours were judged as C, and test times not exceeding 250 hours were judged as D. The results are shown in the high temperature characteristics column in Table 1.

[0054] (evaluation) No. 12 is a sample containing 100 mol % organic compound and 0 mol % inorganic compound, and corresponds to the prior art in which a film containing silicone is provided on the active material. Sample No. 12 was judged as D for high temperature properties, while samples Nos. 1-9 and 11, which contain organic and inorganic compounds, were judged as A, B or C for high temperature properties. It was confirmed that an electrode containing an active material on whose surface a film containing a silicon-bonded organic compound and a silicon-bonded inorganic compound is formed can improve high temperature properties, i.e., can improve thermal stability.

[0055] The samples No. 1-8, 10, and 12 were judged to have an initial resistance of A or B. Samples No. 1-8, 10, and 12 had an inorganic compound molar ratio in the range of 0-75 mol%, an organic compound molar ratio in the range of 25-100 mol%, and a Si atomic concentration in the range of 0.19-1.12 atm%. It was confirmed that a film provided on an electrode that is unlikely to impede the diffusion of lithium ions and can reduce internal resistance must have an inorganic compound molar ratio in the range of 0-75 mol%, an organic compound molar ratio in the range of 25-100 mol%, and a Si atomic concentration in the range of 0.19-1.12 atm%.

[0056] The samples Nos. 1-6, 9, and 11 were judged to have high-temperature properties of A or B. Samples Nos. 1-6, 9, and 11 had an inorganic compound molar ratio in the range of 27-92 mol%, an organic compound molar ratio in the range of 8-73 mol%, and a Si atomic concentration in the range of 0.46-2.50 atm%. It was confirmed that a film provided on an electrode that has high thermal stability, is resistant to deterioration at high temperatures, and can ensure durability must have an inorganic compound molar ratio in the range of 27-92 mol%, an organic compound molar ratio in the range of 8-73 mol%, and a Si atomic concentration in the range of 0.46-2.50 atm%.

[0057] Sample No. 1-9 was in the AC range for both the initial resistance and high temperature characteristics. Sample No. 1-9 had an inorganic compound molar ratio in the range of 27-75 mol%, an organic compound molar ratio in the range of 25-73 mol%, and a Si atomic concentration in the range of 0.19-2.50 atm%. It was confirmed that a film provided on an electrode that can reduce internal resistance and ensure durability needs to have an inorganic compound molar ratio in the range of 27-75 mol%, an organic compound molar ratio in the range of 25-73 mol%, and a Si atomic concentration in the range of 0.19-2.50 atm%.

[0058] Sample No. 1-6 was judged to be A or B for both initial resistance and high temperature characteristics. Sample No. 1-6 had an inorganic compound molar ratio in the range of 27-75 mol%, an organic compound molar ratio in the range of 25-73 mol%, and a Si atomic concentration in the range of 0.46-1.12 atm%. Therefore, it was confirmed that a film provided on an electrode that can further reduce internal resistance and ensure durability needs to have an inorganic compound molar ratio in the range of 25-73 mol%, an organic compound molar ratio in the range of 25-73 mol%, and a Si atomic concentration in the range of 0.46-1.12 atm%.

[0059] The present invention has been described above based on an embodiment, but the present invention is in no way limited to the above embodiment, and it can be easily inferred that various improvements and modifications are possible within the scope of the present invention without departing from the spirit of the present invention.

[0060] In the embodiment, the electricity storage device 10 has been described as including a positive electrode 15 having an active material layer 17 provided on one side of a current collector 16, and a negative electrode 11 having an active material layer 13 provided on one side of a current collector 12, but the present invention is not necessarily limited to this. For example, it is of course possible to apply each element in the embodiment to an electricity storage device including an electrode layer (so-called bipolar electrode) having an active material layer 13 and an active material layer 17 provided on both sides of a current collector. If bipolar electrodes and separators 14 are alternately stacked and housed in a case (not shown), an electricity storage device with a so-called bipolar structure can be obtained.

[0061] In the embodiment, the negative electrode 11 (electrode) in which the active material layer 13 is provided on one side of the current collector 12 has been described, but the present invention is not necessarily limited to this. It is of course possible to provide the active material layer 13 on both sides of the current collector 12. [Explanation of symbols]

[0062] 10. Energy storage devices 11 Negative electrode 12 Current collector 13 Active material layer 18 Active material 19 membrane 21 Inorganic compounds 22 Organic compounds

Claims

1. A current collector and an active material layer attached to the current collector, The active material layer contains an active material, An electrode in which at least a part of a surface of the active material is covered with a film, The membrane is an electrode comprising a silicon-bonded organic compound and a silicon-bonded inorganic compound.

2. 2. The electrode of claim 1, wherein the molar ratio of said organic compound to said inorganic compound is from 25:75 to 75:

25.

3. 3. The electrode according to claim 1, wherein the atomic concentration of silicon contained in said film is 0.1 atm % or more.

4. 3. The electrode according to claim 1, wherein the active material is at least one selected from the group consisting of porous carbon, natural graphite, artificial graphite, graphitizable carbon, non-graphitizable carbon, and carbon fiber.

5. An electricity storage device comprising the electrode according to claim 1 or 2.

Citation Information

Patent Citations

  • Electrode, power storage device, electronic equipment, and method for manufacturing electrode

    JP2016081922A